2015
DOI: 10.1016/j.jvs.2015.04.423
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal degeneration of the thoracoabdominal aorta after medical management of type B aortic dissections

Abstract: Although medical management of uncomplicated acute, type B aortic dissections has been the standard of care, at 5 years, a significant number of patients will require operative intervention for aneurysmal degeneration. Further studies of early intervention (eg, thoracic endovascular aortic repair) for type B aortic dissection to prevent late aneurysm formation are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 35 publications
(53 reference statements)
1
35
0
1
Order By: Relevance
“…19 Indeed, a recent study from our institution looked at 200 patients with medically managed TBAD and found that 51% of patients experienced aortic growth at 5 years and 28% required operative intervention (most were open thoracoabdominal aneurysm repairs) for aneurysmal degeneration. 20 TEVAR has been shown to reduce this risk by promoting remodeling of the aorta through true lumen expansion and false lumen thrombosis in the stented segment of the aorta. 11 In addition, a recent report from the IRAD registry compared 1129 consecutive patients with TBAD and found that patients who had their entry tear sealed with TEVAR had a survival advantage at 5 years over those who were treated with medical therapy alone (85% TEVAR vs 71% medical; P ¼ .018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Indeed, a recent study from our institution looked at 200 patients with medically managed TBAD and found that 51% of patients experienced aortic growth at 5 years and 28% required operative intervention (most were open thoracoabdominal aneurysm repairs) for aneurysmal degeneration. 20 TEVAR has been shown to reduce this risk by promoting remodeling of the aorta through true lumen expansion and false lumen thrombosis in the stented segment of the aorta. 11 In addition, a recent report from the IRAD registry compared 1129 consecutive patients with TBAD and found that patients who had their entry tear sealed with TEVAR had a survival advantage at 5 years over those who were treated with medical therapy alone (85% TEVAR vs 71% medical; P ¼ .018).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that most comorbidities, such as hypertension and coronary artery disease, do not predict aneurysm growth, so it will most likely be anatomic factors that prompt early intervention. 20 The goal of this study was to help establish anatomic parameters that can guide clinical decision-making as to the worth of early TEVAR in uncomplicated TBAD. A previously published report from our institution showed that a total aortic diameter >35 mm correlated with the development of aneurysmal degeneration over time.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%
“…Acute type B aortic dissection (TBAD) is a life-threatening condition with characteristics of sudden onset, rapid progression, and high mortality. 1,2 Benefiting from the lower perioperative mortality than open surgery, thoracic endovascular aortic repair (TEVAR) has become the treatment of choice for acute complicated TBAD. 3,4 Traditionally, patients with uncomplicated TBAD are treated conservatively by controlling hypertension and close monitoring; in other words, the best medical treatment (BMT).…”
Section: See Commentary On Page XXXmentioning
confidence: 99%
“…An aggressive approach to intervention is driven by evidence that the majority of patients with TBAD will fail medical therapy over time, and patients who undergo aortic intervention have a survival advantage over those treated with medical management alone. 8 Advancing chronicity of TBAD increases the complexity of the pathologic anatomy, with septal rigidity and false lumen aneurysmal expansion. Multiple adjunctive procedures at the initial treatment and during follow-up are usually necessary, and no clear end point in therapy has yet been defined for patients with residual false lumen flow.…”
mentioning
confidence: 99%